Sintesis Kitosan Dari Limbah Cangkang Kepiting Dengan Variasi Konsentrasi Naoh Dan Kecepatan Pengadukan - Aisyah Rani; Drastinawati Drastinawati; Yusnimar Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
One parameter that determines the quality of chitosan is the value of deacetylation degree. The degree of deacetylation is influenced by the concentration of NaOH and the stirring speed used in the deacetylation process. The combination of NaOH concentration and the right stirring speed will produce chitosan with a high degree of deacetylation and good quality. The purpose of this study was to determine the effect of using NaOH concentration and the speed of stirring on the characteristics of chitosan produced from crab shells. Crab shells was deproteinated with 3.5% NaOH at 65ºC for 2 hours, the result of deproteination process is crude chitin. Crude chitin was demineralized with 1 N HCl at 30ºC for 1 hour, the result of the demineralization process is chitin. Chitin was deacetylated with NaOH concentration of 40%, 60% and 80%, the deacetylation process took place at a temperature of 120ºC for 3 hours with a stirring speed of 100 rpm, 150 rpm and 200 rpm, the deacetylation process was carried out with two replications. Chitosan obtained was tested by Fourier Transform Infra-Red Spectrophotometer (FTIR). The obtained deacetylation degree of chitosan produced ranged from 70.88% - 85.39%. The chitosan yield produced ranged from 64.5% - 72.3%. The levels of chitosan ash produced ranged from 1.45% - 2%, while the water content of chitosan produced ranged from 1.45% - 2%.Keywords : crab shell, deacetylation. chitosan, FTIR, deacetylation degree